No association between circulating concentrations of vitamin D and risk of lung cancer: an analysis in 20 prospective studies in the Lung Cancer Cohort Consortium (LC3). (2nd April 2018) - Muller, D C; Hodge, A M; Fanidi, A; Albanes, D; Mai, X M; Shu, X O; Weinstein, S J; Larose, T L; Zhang, X; Han, J; Stampfer, M J; Smith-Warner, S A; et al.
Abstract: Background: There is observational evidence suggesting that high vitamin D concentrations may protect against lung cancer. To investigate this hypothesis in detail, we measured circulating vitamin D concentrations in prediagnostic blood from 20 cohorts participating in the Lung Cancer Cohort Consortium (LC3). Patients and methods: The study included 5313 lung cancer cases and 5313 controls. Blood samples for the cases were collected, on average, 5 years before lung cancer diagnosis. Controls were individually matched to the cases by cohort, sex, age, race/ethnicity, date of blood collection, and smoking status in five categories. Liquid chromatography coupled with tandem mass spectrometry was used to separately analyze 25-hydroxyvitamin D2 [25(OH)D2 ] and 25-hydroxyvitamin D3 [25(OH)D3 ] and their concentrations were combined to give an overall measure of 25(OH)D. We used conditional logistic regression to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for 25(OH)D as both continuous and categorical variables. Results: Overall, no apparent association between 25(OH)D and risk of lung cancer was observed (multivariable adjusted OR for a doubling in concentration: 0.98, 95% CI: 0.91, 1.06). Similarly, we found no clear evidence of interaction by cohort, sex, age, smoking status, or histology. Conclusion: This study did not support an association between vitamin D concentrations and lung cancer risk.